On the Road (Again): Commuting and Local Employment Elasticities in Germany - Oliver Krebs; Michael Pflüger (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper develops a quantitative spatial general equilibrium model for the German economy to address two issues. First, we explore the role of commuting for local labor markets and their capacity to absorb productivity shocks. Second, we address the role of housing markets for quantitative analyses. Germany is an exciting laboratory because commuting across local labor markets is pervasive, unique data are available, and because Germany's high degree of trade openness poses a thrilling counterpoint to the United States. Our key findings for German counties are that the employment and resident elasticities associated with local productivity shocks are much above unity, yet disparate (the former larger than the latter), very heterogeneous, and only poorly predicted by simple labor market statistics. Allowing the supply of land/housing to be price elastic increases the elasticities and reinforces our conclusions. The regional heterogeneity of the land/housing shares in Germany turns out to be inessential for our findings, the level of the land/housing share plays an important role, however. We perform a plethora of robustness checks which allow us to gain perspective on extant findings for the United States.
Keywords: F12; F14; R13; R23; 330; quantitative spatial analysis; commuting; migration; employment and resident elasticities